TREN PERKEMBANGAN PENDIDIKAN NON-FORMAL - Ahmad Ahmad; Adelia Jihan Tiara Sari; Ahmad Hadziq Wardana; Moch Nur Ilham Rosyid; Edi Widianto; Ach Rasyad (Jurnal Pendidikan (Teori dan Praktik), 2022)
Non-formal education has a long history in Indonesia, first appearing in the pre-colonial period and continues to grow today. In today's era, the development of non-formal education is very helpful as self-development and improving the quality of learning citizens and can improve the quality of dignity and quality in life. The purpose of this article is to find out the trend of the development of Non-Formal Education in Indonesia. This literature review article uses references sourced from scientific reference articles and books, then analyzed descriptively. The results of after the Indonesian independence revolution in 1945, many non-formal education activities were held, such as eradication of illiteracy, citizenship courses, school broadcasting, women's courses, scouting courses and adult courses conducted in vocational education.